FRET-based and other fluorescent proteinase probes - Hu, Hai-Yu; Gehrig, Stefanie; Reither, Gregor; Subramanian, Devaraj; Mall, Marcus A.; Plettenburg, Oliver; Schultz, Carsten (Biotechnology journal, 2014)
The continuous detection of enzyme activities and their application in medical diagnostics is one of the challenges in the translational sciences. Proteinases represent one of the largest groups of enzymes in the human genome and many diseases are based on malfunctions of proteolytic activity. Fluorescent sensors may shed light on regular and irregular proteinase activity in vitro and in vivo and provide a deeper insight into the function of these enzymes and their role in pathophysiological processes. The focus of this review is on Förster resonance energy transfer (FRET)-based proteinase sensors and reporters because these probes are most likely to provide quantitative data. The medical relevance of proteinases are discussed using lung diseases as a prominent example. Probe design and probe targeting are described and fluorescent probe development for disease-relevant proteinases, including matrix-metalloproteinases, cathepsins, caspases, and other selected proteinases, is reviewed.
Gesehen am 27.10.2020